2x2 Optical Switch Based on Silicon-On-Insulator Microring Resonator - Mardiana, Bidin; Hanim, Abdul Razak; Haroon, Hazura; Sahbudin, Saari; Menon, P.S; Abdullah, H. (Trans Tech Publications, 2012)
In near future, silicon-on-insulator (SOI) microring resonator are expected to be basic components for wavelength filtering and switching due to their compact size and wide free spectral range (FSR). In this paper, a 2X2 optical switch by using active microring resonator is proposed. The switch is consists of second order serially cascaded microring coupled to a pair of waveguide. The ON/OFF state of the design is control by electric signal which will vary the refractive index. The device is design to operate at 1.55μm wavelength. With a 500nm x 200nm rib dimensions, the design is proven to have single mode behaviour. Finite-Difference Time-Domain (FDTD) method simulation by RSOFT software is use to characterize the device performance. The results show that the 2X2 optical switch proposed can be an efficient device to be functioning in WDM application.